2018
DOI: 10.1021/acsami.8b15284
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Microstructure Effect on NO2 Sensors Based on SnO2 Nanoparticles/Reduced Graphene Oxide Hybrids

Abstract: The microstructures of metal oxide-modified reduced graphene oxide (RGO) are expected to significantly affect room-temperature (RT) gas sensing properties, where the microstructures are dependent on the synthesis methods. Herein, we demonstrate the effect of microstructures on RT NO2 sensing properties by taking typical SnO2 nanoparticles (NPs) embellished RGO (SnO2 NPs-RGO) hybrids as examples. The samples were synthesized by growing SnO2 NPs on RGO through hydrothermal reduction (SnO2 NPs-RGO-PR), which disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…SEM image of hydrothermally grown SnO 2 nanoparticles and rGO composites reported by (a) Zhang et al [33] and (b) Peng et al [41]. a high concentration of oxygen vacancy [40,42] and Pt-activated SnO 2 nanoparticles-rGO hybrid [41]. Transmission electron micrograph (TEMs) of SnO 2 quantum dot decorated on rGO surface is represented in Figure 2(a-c).…”
Section: Synthesis Of Graphene/0-d Metal Oxides Compositesmentioning
confidence: 92%
See 3 more Smart Citations
“…SEM image of hydrothermally grown SnO 2 nanoparticles and rGO composites reported by (a) Zhang et al [33] and (b) Peng et al [41]. a high concentration of oxygen vacancy [40,42] and Pt-activated SnO 2 nanoparticles-rGO hybrid [41]. Transmission electron micrograph (TEMs) of SnO 2 quantum dot decorated on rGO surface is represented in Figure 2(a-c).…”
Section: Synthesis Of Graphene/0-d Metal Oxides Compositesmentioning
confidence: 92%
“…Response time and recovery time varied from 1 s to 220 s and 1 s to 1552 s, respectively, as shown in Table 1. Wang et al confirmed that the uniform distribution of SnO 2 nanoparticles on rGO sheets is an effective factor for enhanced NO 2 sensing performances [42]. The p-n junction existed in the interface of nanoparticle and rGO contributed to good room temperature NO 2 sensing properties which is associated with the valid electron flow from SnO 2 nanoparticle to rGO.…”
Section: Summary Of the Performance Of Sensors Fabricated By Using Thmentioning
confidence: 97%
See 2 more Smart Citations
“…In the past few years, graphene-based gas sensing materials have attracted considerable interest because of numerous advantages, such as a high response, short response time, low detection limit, and low working temperature (i.e., room-temperature). [7][8][9] In addition, the distinctive morphology of graphene endues a sensitive response to small changes in an ambient environment, and the functionalization of graphene nanosheets with various "guests" (i.e., organic molecules and nanoparticles) offers a unique selectivity for the resultant gas sensors. [10][11][12][13] It is known that the supramolecular assembly of graphene would retain the inherent structure of graphene and construct a better functional gas sensing scaffold.…”
Section: Introductionmentioning
confidence: 99%